Bone Regeneration of Rat Critical-Sized Calvarial Defects by the Combination of Photobiomodulation and Adipose-Derived Mesenchymal Stem Cells: Photobiomodulation and bone regeneration - Fekrazad, Sepehr; Farzad Mohajeri, Saeed; Mashhadiabbas, Fatemeh; Daghighi, Hooman; Arany, Praveen; Fekrazad, Reza (Journal of Lasers in Medical Sciences, 2024)
Introduction: This study explored the synergistic effects of low-level laser therapy (LLLT) and adipose-derived stem cells (ADSCs) on cranial bone regeneration in rats, addressing the limitations of autogenous grafts and advancing bone tissue engineering with innovative photobiomodulation (PBM) applications. Methods: Sixty Wistar rats were allocated to 5 separate groups randomly; (1) natural bovine bone mineral (NBBM); (2) NBBM+LLLT; (3) NBBM+allogenic ADSCs; (4) NBBM+allogenic ADSCs+LLLT; (5) Only defects. 8-mm calvarial defects were made in each rat in the surgical procedure. A diode laser was applied with the following parameters (continuous mode, power of 100mW, wavelength of 808nm, and 4 J/cm2 energy density) immediately after the procedure and every other day. Bone samples were obtained and assessed histomorphometrically and histologically after staining with hematoxylin and eosin (H&E). Results: Different volumes of bony material were observed in two weeks; 2.94%±1.00 in group 1, 5.1%±1.92 in group 2, 7.11%±2.82 in group 3, 7.34%±2.31 in group 4, and 2.01%±0.83 in group 5 (P<0.05). On the other hand, foreign body residuals were up by 23% in the groups with scaffolding by the end of 2 weeks. Four weeks of observation led to 6.74 %±1.95, 13.24%±1.98, 15.76%±1.19, 15.92%±3.4, and 3.11%±1.00 bone formation in groups 1 to 5, respectively (P<0.05). Generally, the difference between groups 2-4 was not statistically significant based on different types of bone and the extent of inflammation. Conclusion: Bearing in mind the limitations of our research, it was demonstrated that ADSCs in combination with PBM have promising effects on bone tissue regeneration in sizeable bony defects. Furthermore, this study also showed that PBM usage improved the newly regenerated bone quality.